Effects of prenatal stress on the rat hippocampal neurogenesis and the influence of pyramid environment: a morphological and biochemical study - Krishna Dilip Murthy; Perumal Ramasamy; Zainal Arrifin Mustapha; Mitchel Constance George (Universiti Malaysia Sabah, 2012)
Stress is necessary and inevitable, but in excess is deleterious to the physical and mental well-being of any animal species. Stressful experiences during pregnancy lead to development of Impairments that become evident in prepubertal as well as adult stages. Pyramid models constructed with the same base to height ratio as the Great Pyramid of Giza, when aligned on a true north-south axis, is believed to generate, transform and transmit energy which has beneficial effects. The present study was carried out to assess the effects of housing pregnant Sprague Dawley rats subjected to restraint-stress outside (RC) and under the pyramid (RP) as compared to unstressed normal controls (NC) and its effects on the offspring morphometric and physical development, plasma corticosterone levels and hippocampal CA3 pyramidal neuron arborisation. The results showed a delay of one day In the fur appearance, pinna detachment, ear and eye opening In RC which was significant when compared to NC, while there was no such delay In the RP offspring. Significant decrease In head, body and tail length along with decrease in body and brain weight in RC group was also seen when compared to NC, but not In the RP offspring. Significant hypertrophy of adrenal gland and increase in plasma corticosterone was seen in the stressed mothers. The results were similar to those we found In our earlier work on adult rats and mice. Similar hypertrophy of adrenal glands and Increase in plasma corticosterone was also seen at PND 10, 21, 40 and 60 of the offspring's born to the stressed mothers, indicating presence the of stress induced In the HPA axis of the foetus. RC group showed significant decrease at PND 10, 21, 40 and 60 in both the apical and basal dendritic arborisation when compared to NC and RP offspring. The effects were more significant at PND 10 and 21 which Is just before weaning, and the effect became lesser after they were being weaned from the mothers and until adulthood. Thus, the geometric shape of the pyramid and the energy generated within helps reduce the effects of stress probably by suppressing the HPA axis. This study suggests the therapeutic potential of the geometric shape of buildings that could be used to reduce stress and stress related mental diseases. This study prompts us to explore the rehabilitation effects of previously stressed animals under the pyramid in the future.